1983
DOI: 10.1042/bj2150417
|View full text |Cite
|
Sign up to set email alerts
|

The core protein of fibroblast proteoheparan sulphate consists of disulphide-bonded subunits

Abstract: Fibroblast proteoheparan sulphate has a disulphide-bonded subunit structure. The core protein appears to consist of two polypeptides each of Mr 80 000-100 000. As shown elsewhere [Carlstedt, Cöster, Malmström & Fransson (1983) J. Biol. Chem. in the press], both polypeptide molecules carry four to six heparan sulphate side chains (approx. Mr 20 000) and an unknown number of oligosaccharide units, giving the whole macromolecule an Mr in the range 300 000-400 000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…Analysis of the ECM-HSPG through size fractionation indicates the presence of two different PGs (Kavs of 0.25 and 0.41 on Sepharose CL-4B). The sizes of these two species are in good agreement with those reported for other HSPGs isolated from different sources (Coster et al, 1983;Rapraeger and Bernfield, 1985;Mehta et al, 1985), including basement membrane PGs (Hassell et al, 1980;. The two HSPGs present in the ECM of rat skeletal muscles possess two different chain lengths, and preliminary results in our laboratory indicate that the HSPG of Kav = 0.25, which is concentrated in synaptic regions, contains only the GAG chain of 20,000 daltons (Brandan and Inestrosa, unpublished results).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Analysis of the ECM-HSPG through size fractionation indicates the presence of two different PGs (Kavs of 0.25 and 0.41 on Sepharose CL-4B). The sizes of these two species are in good agreement with those reported for other HSPGs isolated from different sources (Coster et al, 1983;Rapraeger and Bernfield, 1985;Mehta et al, 1985), including basement membrane PGs (Hassell et al, 1980;. The two HSPGs present in the ECM of rat skeletal muscles possess two different chain lengths, and preliminary results in our laboratory indicate that the HSPG of Kav = 0.25, which is concentrated in synaptic regions, contains only the GAG chain of 20,000 daltons (Brandan and Inestrosa, unpublished results).…”
Section: Discussionsupporting
confidence: 87%
“…3(A). Two polydisperse peaks of P5S)-material with elution positions of Kav = 0.25 and 0.41 were found [corresponding to Mr = 4-6 x lo5 and 1.5-2.5 x lo5, respectively ;Coster et al (1983) andHassell et al (1985)l. Treatment of these PGs with nitrous acid, broke them down to small fragments that eluted close to the total volume of the column [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reduction and alkylation of the cell-derived macromolecule gave rise to a component with an apparent Mr of 140,000, while the medium-derived form was not affected. Heparan-sulfate lyase treatment of the cell-derived proteoglycan yielded a core protein of apparent Mr 150,000, which, upon reduction, afforded polypeptides of Mr 80,000-100,000 (4 proteoglycans were isolated from the medium and a 4 M guanidinium chloride extract of the cell layer in the presence of proteinase inhibitors (3). Proteoheparan sulfate was purified by isopycnic density-gradient centrifugation in CsCl/4 M guanidinium chloride followed by gel-permeation and ionexchange chromatography after degrading contaminating proteodermatan sulfate with chondroitin ABC lyase in the presence of proteinase inhibitors (3).…”
mentioning
confidence: 99%
“…The gel was first eluted with 0.5 ml each of buffer A and then with 50 mM KPO4 buffer (pH 5.0) containing 0.5 M NaCl and 0.5% (vol/vol) Triton X-100. Bound material was finally displaced with 4 M guanidinium chloride containing 1% (vol/vol) Triton X-100 or with 1% (wt/vol) NaDodSO4.…”
mentioning
confidence: 99%
“…Extraction with lipid solvents has demonstrated that the large size of these molecules is not due to the presence of a lipid subunit as is found on some vertebrate proteoglycans (Norling et al 1981;Schafer et al 1984). Further, failure of reduction and alkylation to separate these sulfated molecules into smaller subunits suggests that the large size does not occur as a result of a protein subunit structure held together by disulfide bonds, which occurs in some vertebrate proteoglycans (Coster et al 1983) and in a nonproteoglycan sulfated glycoprotein from Drosophila (Campbell et al 1987). The presence of sugars in the Dl and DlCL2Bex fractions has been demonstrated by GLC, and sulfation of the polysaccharide chains has been shown by electrophoresis and radioautography.…”
Section: Discussionmentioning
confidence: 97%